A Millennial Perceived Value Towards Sejauh Mata Memandang A Sustainable Fashion Product In Indonesia - Muhammad Iqbal Darmawan; Hezel Judah Sumbayak; Susilowati Natakoesoemah (Syntax Literate, 2022)
As fast fashion contributes to environmental degradation, sustainable fashion has become the counter mechanism for retailers that become contributors to the garment waste promoting slow fashion to the people for a better environment. As for the different intentions the consumers have, purchasing sustainable fashion products means consuming less and only what is needed. Studies explained that in todayâ€™s society consumers have shown an increasing level of ethical concerns in the context of fashion purchase. This includes millennials. As the most influential generation to date, millennials are actively voicing out their concern on social media and are able to drive conversation for example but not limited to sustainable fashion. Therefore, to understand the reason behind millennialsâ€™ intention of purchasing sustainable fashion products, research on millennials' perceived value on one of the leading sustainable fashion products in Indonesia â€œSejauh Mata Memandangâ€ needs to be done. This research will be conducted with a quantitative methodology through purposive sampling. The quantitative method will be conducted by sending a set of questionnaires towards relevant respondents about their perceived value on a sustainable fashion brand. The research shows that sustainable fashion subtypes have a significant impact on the millennialâ€™s perceived value of sustainable fashion products